Engraving of stainless-steel wires to improve optical quality of closed-loop wire-guided flow jet systems for optical and X-ray spectroscopy - Picchiotti, Alessandra; Precek, Martin; Zymaková, Anna; Erichlandwehr, Tim; Liu, Yingliang; Wiste, Tuomas; Kahan, Petr; Fernandez-Cuesta, Irene; Andreasson, Jakob (Frontiers in Molecular Biosciences, 2023)
This paper describes performance enhancement developments to a closed-loop pump-driven wire-guided flow jet (WGJ) for ultrafast X-ray spectroscopy of liquid samples. Achievements include dramatically improved sample surface quality and reduced equipment footprint from 7 × 20 cm2 to 6 × 6 cm2, cost, and manufacturing time. Qualitative and quantitative measurements show that micro-scale wire surface modification yields significant improvements to the topography of the sample liquid surface. By manipulating their wettability, it is possible to better control the liquid sheet thickness and to obtain a smooth liquid sample surface, as demonstrated in this work.